Cardiopulmonary Function Abnormalities in Cohort of Adults following Bronchopulmonary Dysplasia as Preterm Infants - Lasry, Ariane; Kavabushi, Patrick; Canakis, Anne-Marie; Luu, Thuy M.; Nuyt, Anne-Monique; Perreault, Thérèse; Simoneau, Jessica; Landry, Jennifer; Altit, Gabriel (American Journal of Perinatology, 2021)
Objective This study was aimed to describe the cardiopulmonary profiles of adult patients with bronchopulmonary dysplasia (BPD), comparing them to normative adult values.Study Design This study presents a retrospective chart review of all BPD patients followed in the adult BPD clinic, identified from institutional and archive databases, born preterm at ≤33 weeks of estimated gestational age (EGA) between January 1980 and December 2000.Results Forty-four patients with BPD (26.4 ± 2.7 weeks of EGA) were included. Average age at follow-up was 19 years. Majority (61.4%) of the patients had a diagnosis of asthma. Mean spirometry values were: first second of forced expiration (FEV1) 74.1%, forced vital capacity (FVC) 80.7%, and FEV1/FVC 82.5%. Echocardiography (ECHO) images were reviewed, left ventricular (LV) structure and performance did not differ between obstructive and nonobstructive pulmonary function test (PFT) groups, but values of LV longitudinal strain were 4.8% lower than expected normal for adults. Patients with obstructive PFT had additional decreased right ventricular (RV) function by ECHO.Conclusion BPD patients in this study were found to have a burden of cardiorespiratory alterations that persisted into adulthood, with RV performance abnormalities found among patients with obstructive PFT.Key Points
Keywords: prematurity; bronchopulmonary dysplasia; chronic neonatal lung disease; echocardiography; pulmonary vascular disease; extremely low birth weight